The use of the list method in assessing the environmental impact of successive mineral fertilization on the accumulation of some heavy and radioactive pollutants in the soils of Rashidiya sub-district - Abdul Wahhab Majeed Mohammed, Ali (Journal of College of Education, 2021)
The list method has been used in assessing the environmental impact of successive mineral fertilization on the accumulation of some heavy and radioactive elements in the soil and plants growing in Rashidiya district , as the researcher collected several samples of the mineral fertilizers commonly used in Iraq and samples from the soil with different chemical and physical properties , as well as Growing plants and the tomato plant was a model during different periods of cultivation The results of statistical analyzes showed that there were high significant differences between the rates of accumulation of heavy elements with different cultivation periods and soil type The results also indicated that there is a strong correlation relationship at a significant level ( 5% ) between The soil content of heavy elements , the cultivation period and its concentration in the plants growing in it , and the results also showed a significant effect of the type of fertilizer used and added to the soil on the values of its content of heavy and radioactive contaminated elements ( Pb , Ni , U238 , Th232 ) as significant differences were found between the content of nitrogenous fertilizers And phosphate and potassium from those elements , and in general the fertilizer content of heavy pollutant elements ( Pb , Ni ) can be arranged according For the following (MAP < NPK < DAP < TSP ) and from the radioactive elements ( U238 , Th232 ) as follows ( NPK < MAP < DAP < TSP ) and between the analysis test for a wide range of industrial mineral fertilizers produced , some phosphate fertilizers and nutrients of trace elements Phosphate rock contains high levels of cadmium  arsenic lead uranium and thorium compared to other fertilizer types such as nitrogenous potassium and gypsum fertilizers .
Keywords: Environmental Impact Assessment - Mineral fertilization - List method - Heavy and radioactive elements ) .